PENGARUH VARIASI pH DAN RAGI TERHADAP VOLUME DAN KADAR BIOETANOL DARI BAHAN MOLASE - Nurchayati; Sugeng Kuswanto; Tri Rachmanto (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2023)
Energy is a necessity in carrying out economic activities in Indonesia, both for consumption needs and production activities in various business sectors. As a natural resource, energy must be used optimally for the benefit of society and its management must be based on the principles of sustainable development. Bioethanol is a renewable and environmentally friendly energy that can be used as an alternative to fossil fuels. The use of bioethanol as fuel has several advantages, namely the high oxygen content of bioethanol (35%) so that it can produce clean fuel. The purpose of this study was to determine the effect of variations in pH and yeast on the volume and content of bioethanol from molasses material using and the drying time used was 48 hours. From variations in pH and yeast, 9 types of treatment were obtained with 3 repetitions so that the total sample was 27. From the results of the study, the average volume of alcohol produced was at most 550.67 ml in the yeast mass treatment 10 gr/l with a pH of 4.5 and the least was in the yeast mass treatment 15 gr/l with a pH of 4.2 of 432 ml. Whereas the highest average yield was 91.67% for yeast mass of 10 gr/l with a pH of 4.2 and the lowest was found for yeast mass of 15 gr/l with a pH of 4.8 of 88.33%.